Pengaruh Kompetensi,Komunikasi,Disiplin Kerja Terhadap Roduktivitas Karyawan PT Grha Ferry Industri - Roby Firdaus; Rita Srihasnita (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to determine the ef ect of competence, communication and work discipline on employee work productivity. The population used in this study were all employees of PT Grha Ferry Industry. This studyused 60 respondents, using the sample technique. Hypothesis testing in this study used statistical analysis consistingof validity test, reliability test, classical assumption test, t test, F test (hypothesis test) and multipledetermination coef icient (R2) using SPSS (Statistics Product and Service Solution) software version25. Theresearch data came from primary data and were taken by distributing questionnaires. The results of this studyindicate that competence has a significant influence on employee productivity, communication has a significant influence on employee productivity. and work discipline has a significant influence on employee productivity, Simultaneously all variables, namely competence, communication and work discipline have a significant influence on employee work productivity at PT Grha Ferry Industry, Sijinjung Regency